The The Canvas model in project formulation - Ferreira Herrera, Diana Carolina (Cooperativismo & Desarrollo, 2016)
Purpose: The aim of this article is to determine the relevance of the Canvas methodology in project formulation through model characterization, thus answering the question: Is the Canvas methodology a relevant model for project management in an entrepreneurial context? Description: The Canvas model seeks to manage projects as business units. It is a model intended for emphasizing the entrepreneurial potential in project management. For this, texts and articles that have provided the basis for working on such methodology and other older references, which have set the guidelines to discuss business plans and models, are reviewed. Point of view: The innovative and entrepreneurial context in which businesses are conducted today creates the need for simple, dynamic models that promptly react to changes in the environment and provide an organized view of the information available. Conclusions: The Canvas model is a relevant tool in a context of entrepreneurship and innovation and, while the business plan is important, it must be flexible and ready to respond to opportunities and needs (such as the signing of Messi on a napkin).
Keywords: canvas; entrepreneurship; business model; business plan.